Dietary protein-energy restriction followed by restitution with or without fortification in growing rats | IJB 2021 - Ambroise, Akpoue, N’zi (My University, 2022)
This study aimed to assess the effects of a fortified diet on nutritional indicators of growing rats undergoing a protein-energy restriction. For this purpose, three experiments of 30 days were carried out. The first experiment was performed to evaluate the effects of a protein-energy restriction on the growth of 24 rats. The second experiment was intended to rehabilitate by restitution with appropriate diets 24 rats after a period of restriction. The last one was performed on 18 rats with a fortified restitution diet. After two weeks, protein-energy restriction induced a sharp drop in rat growth from the beginning to the end of the experiment. The average values of the nutritional characteristics of treated rats were lower than those of control rats. After protein-energy restitution, the daily average values of the nutritional characteristics of treated rats resume slightly. The restitution with fortification leads to a great resumption of growth and a consequent increase in nutritional characteristics of rats. In conclusion, for protein-energy restitution to be effective, it must be fortified with a complex of essential amino acids and trace elements.
Supplemental Materials: https://osf.io/xur4b/
Keywords: fortification; growth; ijb; innspub; protein-energy; Rats; restitution; restriction